PaTH Forward: A Randomized, Double-Blind, Placebo-Controlled Phase 2 Trial of TransCon PTH in Adult Hypoparathyroidism - Aliya Khan; Lars Rejnmark; Mishaela R. Rubin; Peter Schwarz; Tamara Vokes; B.L. Clarke; Intekhab Ahmed; Lorenz C. Hofbauer; Claudio Marcocci; Uberto Pagotto; Andrea Palermo; Erik Fink Eriksen; et al. (2021)
Context: Hypoparathyroidism is characterized by insufficient levels of parathyroid hormone (PTH). TransCon PTH is an investigational long-Acting prodrug of PTH(1-34) for the treatment of hypoparathyroidism. Objective: This work aimed to investigate the safety, tolerability, and efficacy of daily TransCon PTH in adults with hypoparathyroidism. Methods: This phase 2, randomized, double-blind, placebo-controlled 4-week trial with open-label extension enrolled 59 individuals with hypoparathyroidism. Interventions included TransCon PTH 15, 18, or 21 μg PTH(1-34)/day or placebo for 4 weeks, followed by a 22-week extension during which TransCon PTH dose was titrated (6-60 μg PTH[1-34]/day). Results: By Week 26, 91% of participants treated with TransCon PTH achieved independence from standard of care (SoC, defined as active vitamin Dâ =â 0 μg/day and calcium [Ca]â ≤â 500 mg/day). Mean 24-hour urine Ca (uCa) decreased from a baseline mean of 415 mg/24h to 178 mg/24h by Week 26 (nâ =â 44) while normal serum Ca (sCa) was maintained and serum phosphate and serum calcium-phosphate product fell within the normal range. By Week 26, mean scores on the generic 36-Item Short Form Health Survey domains increased from below normal at baseline to within the normal range. The Hypoparathyroidism Patient Experience Scale symptom and impact scores improved through 26 weeks. TransCon PTH was well tolerated with no treatment-related serious or severe adverse events. Conclusion: TransCon PTH enabled independence from oral active vitamin D and reduced Ca supplements (≤â 500 mg/day) for most participants, achieving normal sCa, serum phosphate, uCa, serum calcium-phosphate product, and demonstrating improved health-related quality of life. These results support TransCon PTH as a potential hormone replacement therapy for adults with hypoparathyroidism.